THE VALIDITY OF USED GOODS AUCTION PRACTICES ON FACEBOOK PLATFORM: A STUDY OF GHARAR AND TADLIS THEORY - Syifa Un Nafsi; Fahmi, Chairul; Azmil Umur (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This study analyzes the validity of used goods auction practices through social media Facebook from the perspective of Islamic law, focusing on the existence of elements of gharar (unclarity) and tadlis (fraud). The author uses a qualitative research method with an empirical approach to understand social problems or human problems based on the creation of holistic images formed with words, reporting the views of informants in detail, and arranged in a scientific setting. Online auctions are a popular alternative to buying and selling, but often cause problems related to the clarity of goods and the transparency of the auction process. The practice of gharar is found in incomplete descriptions of goods, while tadlis occurs through price manipulation by sellers or auction participants. In Islamic law, the validity of an auction depends on the fulfillment of the pillars and conditions of buying and selling, including the clarity of the object, price, and honesty of the parties to the contract. This study emphasizes the importance of transparency, fairness, and openness in online auctions to ensure compliance with sharia principles, thus creating fair transactions and avoiding losses for the parties involved.